Exposure to nanopolystyrene and its 4 chemically modified derivatives at predicted environmental concentrations causes differently regulatory mechanisms in nematode Caenorhabditis elegans. (October 2022) - Qu, Man; Chen, He; Lai, Hanpeng; Liu, Xing; Wang, Dayong; Zhang, Xing
Abstract: Nanoplastics represented by nanopolystyrene (NPS) and its chemically modified derivatives are environmentally ecotoxicological hotpots in recent years, but their toxicity and underlying mechanisms have not been fully identified. Here we employed Caenorhabditis elegans as an animal model to systematically compare the toxicity between nanopolystyrene and its 4 chemically modified derivatives (PS-PEG, PS-COOH, PS-SOOOH and PS-NH2 ) at predicted environmental concentrations. Our study demonstrated that compared with PS exposed group, PS-NH2 exposure (15 μg/L) caused a significant decline in lifespan by suppressed DAF-16/insulin signaling and shortened body length by inhibiting DBL-1/TGF β signaling. Different from PS-NH2 exposed group, PS-SOOOH exposure (15 μg/L) could not cause changes in lifespan, but shortened body length by inhibiting DBL-1/TGF β signaling. In addition, PS-COOH, PS-SOOOH or PS-NH2 exposure (1 μg/L or 15 μg/L) caused more serious toxicity in reducing locomotion behavior and causing gut barrier deficit. Hence the rank order in toxicity of PS-NH2 ＞PS-SOOOH＞PS-COOH＞PS＞PS-PEG was identified. Furthermore, we also presented evidence to support the contention that the observed toxic effects on nematodes were linked to oxide stress and activation of anti-oxidative molecules for reversing the adverse effects induced by nanopolystyrene and its 4 chemically modified derivatives. Our data highlighted nanoplastics may be charge-dependently toxic to environmental organisms, and the screened low toxic modification may support polystyrene nanoparticles continued application for daily consumer goods and biomedicine. Graphical abstract: Image 1 Highlights: We evaluates the toxicity between PS and PS-PEG, PS-COOH, PS-SOOOH and PS-NH2 at predicted environmental concentrations. Toxicity order: PS-NH2 ＞PS-SOOOH＞PS-COOH＞PS＞PS-PEG. A low toxicity of PEG modification on PS is screened out. Differently regulatory mechanisms of C. elegans exposed to PS and its 4 modified derivatives are further identified. Our data reveal that nanoplastics may be charge-dependently toxic to environmental organisms.